Correlation between transverse maxillary discrepancy and the inclination of first permanent molars. a pilot study - Mulett-Vásquez, Jackeline; Clavijo-Escobar, Andres Felipe; Fuentes-Loyo, Isabela; Sánchez-Cano, Paula Andrea (Revista Facultad de Odontología Universidad de Antioquia, 2017)
Introduction: the development and growth of craniofacial structures allow some dental alterations to be compensated with maxillary reactions. The purpose of this study was to correlate transversal maxillo-mandibular discrepancy with the bucco-lingual inclinations of first permanent maxillary and mandibular molars in a population aged 10 to 16 years, by means of cone beam computed tomography (CBCT). Methods: the sample included 18 CT scans of patients selected by convenience, prior authorization from the radiographic center and with validation of the Bioethics Committee of Universidad Autónoma de Manizales (Agreement No. 51, 2015). The transverse mandibular and maxillary distance was measured, calculating discrepancy and correlating with the bucco-lingual inclination of first permanent molars. Results: average mandibular transverse distance was higher than maxillary transverse distance (p < 0.05). On average, lower molars had greater inclination degree than upper molars. Average discrepancy rate was 1.86 mm (0.90 mm-2.82 mm CI). The analysis grouped by discrepancy type showed significant correlations between positive maxillary discrepancy (> 5º) and the inclination of molars (p < 0.05). There was also moderate correlation in patients with negative maxillary discrepancy (< 5º). Conclusion: transverse maxillomandibular discrepancy is related to the bucco-lingual inclination of first permanent maxillary and mandibular molars in two different ways according to discrepancy type—positive or negative—. The reaction of the maxillary is a process that requires more studies to understand the timing and extent of the adaptation.